The influence of community norms on black officers’ decision-making in a large municipal police department in a majority minority United States city: a quasi-experiment - LaFrance, Casey (Journal of ethnicity in criminal justice, 2021)
For decades, scholars have called for and investigated the effects of representative bureaucracy, with some scholars explaining that common lived experiences, or “subject positions” between street-level bureaucrats and community members might facilitate better communication that in turn could lead to consensus or shared meaning in discourse and behavior between these two groups. Building upon the theoretical scaffolding of the Target Model of discretion, our study uses self-reported survey data from 190 sworn officers in a large majority minority city in the southern United States to investigate the relationship between officer race and the priority Black and non-Black officers ascribe to community norms and expectations as influences on their decision-making processes. Our findings indicate that Black police officers in this city are significantly more likely than their non-Black counterparts to recognize community norms as a factor that influences their decisions, in line with the research hypothesis.